Group decision via usage of analytic hierarchy process and preference aggregation method (Keputusan berkumpulan menggunakan proses hierarki analisis dan kaedah pengagregatan keutamaan) - Langroudi Majid Zerafat Angiz,; Adli Mustafa,; Noraida Abdul Ghani,; Anton Abdulbasah Kamil, (Universiti Kebangsaan Malaysia, 2012)
The Analytic Hierarchy Process (AHP) is a recognised modern approach to solve decision making problems. Initially introduced by Saaty in 1971 as a tool for handling individual decision making situation, the method has since been extended to incorporate groups. In this paper, a new method for AHP group decision making is proposed. The method integrates AHP with a Data Envelopment Analysis (DEA)-based preferential aggregation method. It manipulates the preferential weights and ranking aspect of each decision maker in coming up with an optimisation model that determines the best efficiency score of each alternatives. These efficiency scores are then used to rank the alternatives and determine the group decision weights. A comparative analysis of the method with another AHP group decision making method indicates a similar ‘satisfactory index’ level.